MONETARY POLICY AND STOCK PRICE BEHAVIOUR OF BANKS IN NIGERIA: A PANEL DYNAMIC CO-INTEGRATION APPROACH (Practitioner Research, 2023)
This study was conducted to examine effect of monetary policy on stock prices of listed banks in Nigeria. Specifically, the study examined effects of broad money supply, Treasury bill rate, monetary policy rate, exchange rate, cash reserve ratio, lending rate and savings deposit rate on stock prices of 15 listed banks on the Nigerian Stock Exchange as at 31st December, 2019. The study employed descriptive statistics, panel dynamic ordinary least squares and panel causality analysis to analyze quarterly data of stock price (STP) and monetary policy variables from 2006 to 2019. Results of the panel dynamic ordinary least squares (PDOLS) show that for banks, broad money supply (M2), monetary policy rate (MPR), exchange rate (EXCH) and interest on savings (SDR) significantly affect stock price negatively (p =0.0147; p =0.0000; p = 0.0110 and p = 0.0003 for M2, MPR, EXCH and SDR respectively). Treasury bill rate (TBR) significantly affects stock price positively (p = 0.0000) while cash reserve ratio (CRR) and lending rate (LDR) have insignificant effect on stock prices of banks. We recommend that Nigerian banks should be more pro-active in managing effects of monetary policy announcements to avert prolonged negative effects of such policies on their stock prices. We also advocate a re-appraisal of MP tools vis-à-vis stock market expansion goal by the Central Bank of Nigeria.